ReFocus : films of Rachid Bouchareb - Gott, Michael; Kealhofer-Kemp, Leslie (ReFocus: the international directors series., 2020)
ReFocus: The Films of Rachid Bouchareb is the first book-length study of the internationally recognized director's films. Bouchareb was one of France's first filmmakers of North African descent and his career as a director and producer now spans over 35 years. Remarkably varied in their themes, formal elements and narrative settings, Bouchareb's work has engaged with and reflected on a variety of crucial social, political and historical issues; from the role of colonial troops in the French army during the Second World War, to terrorism in contemporary Europe. This volume examines Bouchareb's films from an interdisciplinary perspective, exploring key influences on his output and considering new theoretical approaches to his filmmaking.